The Effect of Massage on Pain Reduction in Osteoarthritis Knee: Literature Review - Khairina Afrida, Hasya; Dheirani, Dheby; Adi P, Imam Cahyo; Wicksono, Ganjar Pujo; Alpiah, Dini Nur (International Journal of Social Research, 2024)
One way to reduce OA complaints is by using massage methods. Massage is a condition of physical recovery from certain disorders or diseases through muscle and physical straightening techniques so that this method has good credibility. Massage is the art of hand movement that aims to get pleasure and maintain health. This mechanical hand movement will create a sense of calm and comfort for the recipient. This study aims to determine the effect of massage on pain relief in knee osteoarthritis. This study uses a critical review approach, carried out using a PICO search in several databases such as Google Scholar, PubMed, and Scimago. From that search, 5 journals were obtained which showed that the frequency was 2 times a week, with a duration of 20 minutes, carried out 2 times a week for 8 weeks. With p<0.001 showed significant results in relieving pain in osteoarthritis patients.